2016
DOI: 10.3892/ol.2016.4239
|View full text |Cite
|
Sign up to set email alerts
|

Label-free discrimination of different stage nasopharyngeal carcinoma tissue based on Raman spectroscopy

Abstract: Abstract. The present study aimed to evaluate a label-free tissue test for the detection of nasopharyngeal carcinoma (NPC) at early and advanced stages using Raman spectroscopy (RS). RS measurements were performed to acquire high quality Raman spectra on two groups of tissue samples: One group consists of 30 NPC patients at the early stages (I-II), and the other group is 46 NPC patients at the advanced stages (III-IV). Tentative assignment of Raman bands showed specific biomolecular changes associated with can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…[ 2 ] Specifically, Raman band intensity from cancerous nasopharyngeal tissues increased at 1,268, 1,579, and 1,660 cm −1 , referring to a higher quantity of proteins, lipids, and nucleic acids in the cancerous cells. [ 22 ] Our results showed that with increase of GSK2334470 concentration, the Raman intensity decreased at 781 cm −1 (cytosine/uracil ring breathing mode of nucleotide), [ 23 ] 1,084 cm −1 (phosphodiester groups of nucleic acids), [ 24 ] 1,263 cm −1 (thymine, adenine; =C‐H bending mode of phospholipids), [ 22,25,26 ] 1,304 cm −1 (CH 2 twisting mode of lipids, adenine, cytosine), [ 27 ] and 1,655 cm −1 (C=O stretching mode of amide I proteins, α‐helix conformation, C=C stretching mode of lipids). [ 27,28 ] Such decrease in the Raman band intensities indicated that the GSK2334470 at certain concentrations could interrupt the synthesis of nucleic acid and protein in the MCF‐7 cells and reduce their intracellular quantity.…”
Section: Discussionmentioning
confidence: 98%
“…[ 2 ] Specifically, Raman band intensity from cancerous nasopharyngeal tissues increased at 1,268, 1,579, and 1,660 cm −1 , referring to a higher quantity of proteins, lipids, and nucleic acids in the cancerous cells. [ 22 ] Our results showed that with increase of GSK2334470 concentration, the Raman intensity decreased at 781 cm −1 (cytosine/uracil ring breathing mode of nucleotide), [ 23 ] 1,084 cm −1 (phosphodiester groups of nucleic acids), [ 24 ] 1,263 cm −1 (thymine, adenine; =C‐H bending mode of phospholipids), [ 22,25,26 ] 1,304 cm −1 (CH 2 twisting mode of lipids, adenine, cytosine), [ 27 ] and 1,655 cm −1 (C=O stretching mode of amide I proteins, α‐helix conformation, C=C stretching mode of lipids). [ 27,28 ] Such decrease in the Raman band intensities indicated that the GSK2334470 at certain concentrations could interrupt the synthesis of nucleic acid and protein in the MCF‐7 cells and reduce their intracellular quantity.…”
Section: Discussionmentioning
confidence: 98%
“…Hence, the LVs could explain the diagnostic relevant variations rather than the significant differences in the dataset. Many studies have constructed and validated this statistical model to predict the sensitivity and specificity of Raman system in NPC model [ 15 , 23 , 24 ]. Additionally, consistent and reproducible results using this statistical model have been validated in various cancers including, gastric cancer [ 11 , 12 ], esophageal cancer [ 11 , 25 ], colon cancer [ 21 , 26 ] and NPC [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Raman spectral differences between pathological and physiological tissues are usually subtle with apparently spectral overlapping. [12][13][14][15][16][17][18][19] Therefore, powerful and robust spectral data processing and diagnostic algorithms are needed to extract the most diagnostically significant Raman spectral features and make them accurately correlated with histopathology. Generally, multivariate statistical analysis methods are used to classify Raman spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, multivariate statistical analysis methods are used to classify Raman spectra. [14][15][16][17][18][19][20] However, a drawback associated with these methods is that they require lots of spectral preprocessing including smoothing, baseline correction and peak detection, which has the potential risk of smoothing the underlying Raman features and thus compromising their discriminative utility. In addition, traditional classification methods lack a powerful feature learning ability, and the correct identification rate highly depends on valid feature wavelength extraction.…”
Section: Introductionmentioning
confidence: 99%